Bortezomib in multiple myeloma management - Hrishik Iqbal; Mohammad Nazmul Islam; Srikumar Chakravarthi; Mohammad Chand Jamali; Rezwan Ahmed Mahedi; Sadia Afrin; Pujita Roy; Fahadul Alam; Md.Shajalal Reza; Νikolaos Syrmos (Faculty of Medicine, Universitas Trisakti, 2025)
Multiple myeloma (MM) is a hematologic malignancy characterized by the uncontrolled proliferation of plasma cells, leading to complications such as bone lesions, renal dysfunction, and immune suppression. Over the past three decades, its incidence has risen significantly, attributed to factors such as aging populations and improved diagnostic methods. Treatment strategies have evolved considerably, transitioning from alkylating agents and high-dose chemotherapy to targeted therapies, including proteasome inhibitors (PIs) and immunomodulatory drugs (IMiDs). Bortezomib, a first-in-class PI, has revolutionized MM management by inhibiting proteasome activity, thereby inducing apoptosis in malignant plasma cells. This review evaluates the efficacy, safety, and clinical applications of bortezomib, both as monotherapy and in combination with dexamethasone, IMiDs, and conventional chemotherapies. Key clinical trials, such as VISTA and SUMMIT, demonstrate its superiority over traditional regimens, improving response rates and survival outcomes. However, its use is associated with adverse effects, including peripheral neuropathy, hematologic toxicities, and gastrointestinal disturbances, necessitating dose modifications and supportive care. Emerging combinations with monoclonal antibodies and novel agents further enhance therapeutic potential, though optimal sequencing remains under investigation. Systematic literature search was performed using PubMed and Cochrane to identify relevant studies on the applications of bortezomib. The search was inclusive of all publications up to May 2025, without restriction by publication year, to ensure a thorough review of research on bortezomib. Studies focusing on multiple myeloma (MM) and the efficacy of bortezomib were prioritized. A broad set of keywords was employed reflecting the diverse applications of bortezomib in MM treatment. The search strategy was designed to capture a wide range of relevant studies. By synthesizing evidence from 77 studies, this review highlights bortezomib’s pivotal role in MM treatment while addressing challenges in toxicity management. Future research should focus on refining combination strategies and minimizing side effects to maximize long-term patient outcomes.